2020
DOI: 10.4236/pp.2020.118015
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Aqueous Solubility and Antibacterial Activity of Cefuroxime Axetil Using Microcrystalline Cellulose as Carrier

Abstract: This investigation was undertaken to enhance the solubility and consequent antibacterial activity of cefuroxime axetil (CA), a β-lactamase-stable broad spectrum second generation cephalosporin through solid dispersion (SD) technique. For this purpose, CA loaded SDs (CSDs) were prepared by solvent evaporation method using different concentrations of microcrystalline cellulose (MCC) as carrier. The CSDs were characterized by in-vitro dissolution study, thermal analysis (DSC), crystallinity (PXRD), interactions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…(2012) also found that employing porous carrier sylysia 350 to prepare solid dispersions enhanced CA solubility, dissolution rate, flowability, and compressibility significantly [32]. Salam MT et al (2020) suggested a solid dispersion formulation with improved solubility and antibacterial action employing microcrystalline cellulose (Avicel PH 102) as the carrier [33].…”
Section: Discussionmentioning
confidence: 99%
“…(2012) also found that employing porous carrier sylysia 350 to prepare solid dispersions enhanced CA solubility, dissolution rate, flowability, and compressibility significantly [32]. Salam MT et al (2020) suggested a solid dispersion formulation with improved solubility and antibacterial action employing microcrystalline cellulose (Avicel PH 102) as the carrier [33].…”
Section: Discussionmentioning
confidence: 99%